2020
DOI: 10.1186/s12969-020-00455-4
|View full text |Cite
|
Sign up to set email alerts
|

Prefilled pen versus prefilled syringe: a pilot study evaluating two different methods of methotrexate subcutaneous injection in patients with JIA

Abstract: Background Methotrexate is the most commonly used disease-modifying antirheumatic drug recommended in the treatment of juvenile idiopathic arthritis. It can be administered orally or subcutaneously, the latter method is associated with fewer side effects and higher drug bioavailability. Nevertheless, the pain associated with injection is a considerable drawback of this treatment option in the pediatric population. Currently, there are two single-use subcutaneous injection devices available: the pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…Although pediatric populations were not the focus of this scoping review, the use of MTX injections in children with juvenile idiopathic arthritis has been investigated. Similar to our findings in adult populations (48,52), pediatric populations generally prefer prefilled MTX pens over prefilled syringes, citing less pain as the primary reason for such a preference (64). Autonomy in taking medicine was valued by young adults with inflammatory arthritis as highlighted by Hart et al (65), which was similar to our findings in older patients.…”
Section: Discussionsupporting
confidence: 89%
“…Although pediatric populations were not the focus of this scoping review, the use of MTX injections in children with juvenile idiopathic arthritis has been investigated. Similar to our findings in adult populations (48,52), pediatric populations generally prefer prefilled MTX pens over prefilled syringes, citing less pain as the primary reason for such a preference (64). Autonomy in taking medicine was valued by young adults with inflammatory arthritis as highlighted by Hart et al (65), which was similar to our findings in older patients.…”
Section: Discussionsupporting
confidence: 89%
“…As far as we have been able to trace, there is little research and development of equipment that suits children with RDs. A recent Polish study, however, showed that children ranked pens as easier to use than syringes and that the level of pain and side effects was significantly lower (Roszkiewicz et al, 2020). A possible bias in this study was that all the participants (n = 23) had used syringes before the introduction of the pens, and the novelty of pens might partly explain the effect.…”
Section: The Technical and Emotional Complexity Of The Training Sessionsmentioning
confidence: 69%
“…In general, most patients prefer a PFP over a PFS because they are convenient, quick, comfortable, and easy to use and because they have built-in safety features [ 24 , 28 , 30 , 32 ]. However, some patients who experience ISP, which may be influenced by pain catastrophizing and can cause dread of injecting over time [ 21 , 29 ], may prefer to use a PFS because the device allows better control over the speed and duration of injection as compared with a PFP [ 31 , 94 ].…”
Section: Methodsmentioning
confidence: 99%